اللغة العربية بإندونيسيا (السياسة، التاريخ، الوضع الحالي - khoirurrijal khoirurrijal (Institut Agama Islam Negeri (IAIN) Metro, 2017)
The Arabic language is spoken by Indonesian society as well as being religious language in the Holy Qur’an. The prestige of this noble life to ensure its existence since the early days of their entry to Indonesia with the simultaneous introduction of Islam. Conclusion of this research can be described as follows: (a). The Arabic language education in Indonesia